2013
DOI: 10.1007/s10237-013-0498-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of load repetition in bone mechanotransduction using poroelastic finite-element models: the impact of permeability

Abstract: Experimental evidence suggests that interstitial fluid flow is a stimulus for mechanoadaptation in bone. Bone adaptation is sensitive to the frequency of loading and rest insertion between load cycles. We investigated the effects of permeability, frequency and rest insertion on fluid flow in bone using finite-element models to understand how these parameters affect the mechanical stimulus. A simplified 3D poroelastic finite-element model of a beam in bending was developed, in order to simulate the behavior of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 51 publications
6
26
0
Order By: Relevance
“…Previous computational studies (Pereira and Shefelbine, 2014) showed that poroelastic models with bone permeability k = 10 −22 m 2 simulate relaxation times similar to in vivo measures in mice and consistent with recent experimental estimations (Benalla et al, 2014).…”
Section: Constitutive Assumptions For Permeability Of Bone and Membranessupporting
confidence: 83%
See 1 more Smart Citation
“…Previous computational studies (Pereira and Shefelbine, 2014) showed that poroelastic models with bone permeability k = 10 −22 m 2 simulate relaxation times similar to in vivo measures in mice and consistent with recent experimental estimations (Benalla et al, 2014).…”
Section: Constitutive Assumptions For Permeability Of Bone and Membranessupporting
confidence: 83%
“…Some of the used constitutive values were estimated or measured for different specimens, as the literature lacks estimation of some poroelastic parameters in murine bone. Pereira and Shefelbine (2014), † Steck et al (2003a), ¶ Dillaman et al (1991) Sensitivity studies (not included in this paper) were conducted to determine the influence of trabecular bone and growth plate stiffness on the calculations of the mechanical environment in the diaphysis. A wide interval of stiffness values was considered for each compartment, ranging from cartilage (10MPa) to cortical bone (17GPa).…”
Section: Materials Propertiesmentioning
confidence: 99%
“…The stress distribution model may be improved by adjusting thresholds that better predict actual clinical scan data and further extended by including a porosity stage that may provide a deeper understanding of the basic mechano-transduction, poroelastic fluid low and cellular signaling. 9 The proposed technique may also be extended using simulated force data derived from biomechanical models of the therapeutic activity – in this case it may even be possible to design and evaluate a candidate FES bone therapy in-silico prior to clinical trials. This is illustrated in Figure 5 where the bi-lateral force actions of the gluteus maximus muscles were biomechanically simulated and added to the quadriceps actions during the drive phase.…”
Section: Resultsmentioning
confidence: 99%
“…Previous computational studies (Pereira and Shefelbine, 2014) showed that poroelastic models with bone permeability k = 10 , for low flow rates, roughly 5 orders of magnitude higher than the permeability of the lacunar-canalicular porosity. The same value was assigned to both surfaces, despite the fact that the literature often characterises the endosteum to be more permeable than the periosteum.…”
Section: Constitutive Assumptions For Permeability Of Bone and Membranesmentioning
confidence: 99%
“…Elastic elements were considered in the rest of the cortical region (blue colour in Figure 7a), where no adaptation was considered. Intrinsic permeability in the poroelastic bone regions was set to k = 10 −22 m 2 (Pereira and Shefelbine, 2014). Osteocyte canaliculi are predominantly oriented longitudinally, rather than transversely (Dillaman et al, 1991), and, therefore, this value was assigned to the longitudinal component, k l .…”
Section: Materials Propertiesmentioning
confidence: 99%